2020
DOI: 10.3389/fpls.2020.612781
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Production of SARS-CoV-2 Related Proteins in Plants: A Proof of Concept for Rapid Repurposing of Indoor Farms Into Biomanufacturing Facilities

Abstract: The current CoVid-19 crisis is revealing the strengths and the weaknesses of the world’s capacity to respond to a global health crisis. A critical weakness has resulted from the excessive centralization of the current biomanufacturing capacities, a matter of great concern, if not a source of nationalistic tensions. On the positive side, scientific data and information have been shared at an unprecedented speed fuelled by the preprint phenomena, and this has considerably strengthened our ability to develop new … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 37 publications
2
55
0
Order By: Relevance
“…Several plant-produced therapeutics ( Kizhner et al, 2015 ; Ma et al, 2015 ; Mor, 2015 ; Prevail Ii Writing Group et al, 2016 ) and vaccines ( Yuki et al, 2013 ; Hendin et al, 2017 ; Donini and Marusic, 2019 ) are currently in pipeline for clinical trials and approval, Notably plant-produced Glucocerebrosidase enzyme (Elelyso TM ) for the treatment of type I Gaucher’s disease has been approved by US Food and Drug Administration ( Fox, 2012 ) and tobacco-derived seasonal flu VLP vaccine from Medicago Inc., is currently in final stages of clinical trial ( Ward et al, 2021 ). Hence, plant-based expression could be an alternative option for rapid production of emergency vaccines or therapeutic antibodies ( Iyappan et al, 2018 ; Diego-Martin et al, 2020 ; Rattanapisit et al, 2020 ; Shanmugaraj and Phoolcharoen, 2021 ; Siriwattananon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several plant-produced therapeutics ( Kizhner et al, 2015 ; Ma et al, 2015 ; Mor, 2015 ; Prevail Ii Writing Group et al, 2016 ) and vaccines ( Yuki et al, 2013 ; Hendin et al, 2017 ; Donini and Marusic, 2019 ) are currently in pipeline for clinical trials and approval, Notably plant-produced Glucocerebrosidase enzyme (Elelyso TM ) for the treatment of type I Gaucher’s disease has been approved by US Food and Drug Administration ( Fox, 2012 ) and tobacco-derived seasonal flu VLP vaccine from Medicago Inc., is currently in final stages of clinical trial ( Ward et al, 2021 ). Hence, plant-based expression could be an alternative option for rapid production of emergency vaccines or therapeutic antibodies ( Iyappan et al, 2018 ; Diego-Martin et al, 2020 ; Rattanapisit et al, 2020 ; Shanmugaraj and Phoolcharoen, 2021 ; Siriwattananon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We expressed an RBD variant that was previously produced in mammalian or insect cells ( Stadlbauer et al, 2020 ; Klausberger et al, 2021 ) and observed low expression levels and high amounts of homodimers. Recombinant SARS-CoV-2 RBD variants have recently been produced in N. benthamiana using different transient expression systems ( Diego-Martin et al, 2020 ; Mamedov et al, 2020 ; Rattanapisit et al, 2020 ; Makatsa et al, 2021 ). Diego-Martin et al (2020) used a MagnICON-based expression vector to produce a His-tagged RBD variant carrying the same amino acid region (R319-F541) as present in our RBD.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant SARS-CoV-2 RBD variants have recently been produced in N. benthamiana using different transient expression systems ( Diego-Martin et al, 2020 ; Mamedov et al, 2020 ; Rattanapisit et al, 2020 ; Makatsa et al, 2021 ). Diego-Martin et al (2020) used a MagnICON-based expression vector to produce a His-tagged RBD variant carrying the same amino acid region (R319-F541) as present in our RBD. In agreement with our data, low yields (2-4 μg/g fresh weight) and considerable amounts of higher molecular weight bands were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The favorable features of this industrial approach have been widely and frequently reviewed, among which speed of production in very large amounts and comparative low costs of productions stand out (Ma et al, 2003;Williams et al, 2014Williams et al, , 2016Moon et al, 2019;Capell et al, 2020;McDonald and Holtz, 2020). In the particular case of SARS-CoV-2 proteins, a few examples showing their production in plants have been published very recently (Diego-Martin et al, 2020;Siriwattananon et al, 2021). A previous approach to produce plant-made viral proteins that could be potentially used as antigens has been shown for the related SARS-CoV, where antibody binding to immobilized plant-produced virus antigen was demonstrated using a limited panel of serum samples (Demurtas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%